Metabolome and Lipidome Profiles of Populus × canescens Twig Tissues During Annual Growth Show Phospholipid-Linked Storage and Mobilization of C, N, and S - Watanabe, Mutsumi; Netzer, Florian; Tohge, Takayuki; Orf, Isabel; Brotman, Yariv; Dubbert, David; Fernie, Alisdair R.; Rennenberg, Heinz; Hoefgen, Rainer; Herschbach, Cornelia (Frontiers in Plant Science, 2018)
The temperate climax tree species Fagus sylvatica and the floodplain tree species Populus x canescens possess contrasting phosphor (P) nutrition strategies. Whilst F. sylvatica has been documented to display P storage and mobilisation (Netzer et al., 2017, Environmental and Experimental Botany), this was not observed for Populus x canescens (Netzer et al., 2018a, Tree Physiology). Nevertheless, changes in the abundance of organic bound P in grey poplar trees indicated adaptation of the P nutrition to different needs during annual growth. The present study aimed at characterizing seasonal changes in metabolite and lipid abundances in grey poplar and uncovering differences in metabolite requirement due to specific needs depending on the season. Seasonal variations in the abundance of (i) sugar-Ps and phospholipids, (ii) amino acids, (iii) sulphur compounds, and (iv) carbon metabolites were expected. It was hypothesised that seasonal changes in metabolite levels relate to N, S and C storage and mobilisation. Changes in organic metabolites binding Pi (Porg) are supposed to support these processes. Variation in triacylglycerols (TAGs), in sugar-phosphates, in metabolites of the TCA cycle and in the amino acid abundance of poplar twig buds, leaves, bark and wood were found to be linked to changes in metabolite abundances as well as to C, N and S storage and mobilisation processes. The observed changes support the view of a lack of any P storage in poplar. Yet, during dormancy, contents of phospholipids in twig bark and wood were highest probably due to frost-hardening and to its function in extra-plastidic membranes such as amyloplasts, oleosomes and protein bodies. Consistent with this assumption, in spring sugar-Ps increased when phospholipids declined and poplar plants entering the vegetative growth period and, hence, metabolic activity increases. These results indicate that poplar trees adopt a policy of P nutrition without P storage and mobilization that is different from their N- and S- nutrition strategies.